2015
DOI: 10.1007/s12159-015-0121-8
|View full text |Cite
|
Sign up to set email alerts
|

Social and environmental risk management in supply chains: a survey in the clothing industry

Abstract: Almost daily, news indicates that there are environmental and social problems in globally fragmented supply chains. Even though conceptualisations of sustainable supply chain management suggest supplier-related risk management for sustainable products and processes as substantial for companies, research on how risk management for environmental and social issues in supply chains is performed has so far been neglected. This study aims at analysing both why companies in the clothing industry are performing manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
96
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 59 publications
4
96
0
10
Order By: Relevance
“…It seems logical to subordinate the two approaches to sustainable risk management. In line with the findings of Freise and Seuring [3], it has been found that both assessment and collaboration have a positive impact on environmental and social performance [19]. Moreover, other forerunning researchers [9,[32][33][34] in socially related research found that increased involvement by purchasing managers in socially responsible activities leads to an enhanced supplier performance [34].…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…It seems logical to subordinate the two approaches to sustainable risk management. In line with the findings of Freise and Seuring [3], it has been found that both assessment and collaboration have a positive impact on environmental and social performance [19]. Moreover, other forerunning researchers [9,[32][33][34] in socially related research found that increased involvement by purchasing managers in socially responsible activities leads to an enhanced supplier performance [34].…”
Section: Introductionsupporting
confidence: 60%
“…These facts automatically lead to increased pressure on apparel retailers to achieve lower costs and shorter lead times, resulting in poor labor standards in the supply chain [4,42]. As a consequence, apparel supply chains are becoming increasingly global [1,43], and the rising level of outsourcing to developing countries [44] has emphasized the focus on sustainability [3][4][5][6]13,45].…”
Section: The Apparel Industry As the Field Of Applicationmentioning
confidence: 99%
See 3 more Smart Citations